ASAS KESEIMBANGAN DALAM ALTERNATIF PENYELESAIAN SENGKETA HUBUNGAN INDUSTRIAL DI LUAR PENGADILAN - Usak . (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Industrial labor disputes between workers or workers and employers often occur as a result of mismatches of opinion and / or actions of both. Both disputes are usually preceded by violations of law and may occur not for violation of the law. For the right institution to resolve industrial relations disputes, if based on the principle of balance thinking is a deliberation to seek dispute resolution, the right institution is a non-litigation institution outside the court, without having to be brought to the Industrial Relations Court. To further ensure the creation of a balance principle for the parties in disputes in industrial relations disputes, according to Law no. 2 of 2004 on Industrial Relations Dispute Settlement, dispute settlement takes priority through negotiation to seek deliberation outside the consensus of the courts, this will create a balance principle for the position of the parties while providing legal protection for workers/laborers. In accordance with the legal matter, the purpose of this study is to examine alternative forms of realization of industrial relations dispute settlement outside the court as a reflection of the principle of equilibrium.